(untitled) (Research, Society and Development, 2026)
This article aims to report the experience of the Programming Club, a project focused on helping and encouraging the fight against the lack of technology integration in schools, promoting inclusive and collaborative environments, guiding the learning and practice of programming, thus enabling the exchange of knowledge and skills among participants. The research adopts a narrative approach, grounded in the experience lived during the project’s execution. The methodology combines theory and practice through partnerships with schools and weekly meetings that included lectures, workshops, group problem-solving, and practical project development. Over six months, 320 students participated, 120 from IFSertãoPE Campus Floresta and 200 from the State Technical School Deputado Afonso Ferraz ETEDAF, aged between 15 and 18 years. The Club also encouraged participation in events and educational activities, strengthening interaction with the programming community. Key results include the partnerships established, in which programming logic classes were taught using VisuAlg 3.0 and Scratch, as well as mini-courses and programming marathons held at IFSertãoPE. Evaluations indicate positive outcomes, such as the strengthening of student leadership and the development of computational thinking among participants.